Application of PhET Simulation-Assisted Problem-Based Learning Model in Improving Students’ Critical Thinking Skills on Rotational Dynamics Material - Mustikazahra, Fadia; Novia, Hera; Aviyanti, Lina (Journal of Educational Sciences, 2025)
This research investigates the effectiveness of the Problem-Based Learning (PBL) model assisted by PhET simulations in enhancing students' critical thinking skills on rotational dynamics. A quasi-experimental design was used in this research, involving two groups: an experimental group using PBL model with PhET simulations and a control group using PBL model without PhET simulations. The research participants were high school students, and data were collected through pre-test and post-test assessments measuring critical thinking skills. The findings indicate that students in the experimental group demonstrated significant improvement. Statistical analysis showed a higher mean score increase in the experimental group compared to the control group. These results suggest that the application of PBL with PhET simulations is an effective approach to fostering critical thinking in physics education, particularly in rotational dynamics.